مقاصد علم أصول الفقه وآثارها في التجديد الأصولي - شرقي فيصل (University of M'Sila, 2025)
علم "أصول الفقه" نشأ ونضج في وسط إسلاميّ محض، ومع مرور الزّمن لوحظ ضعف في التّعامل مع هذا العلم، ممّا استدعى ظهور دعوات إلى تجديده، خاصّة في عصرنا، وهذه الأطروحة تستهدف الكشف عن مقاصد هذا العلم لتكون معيارا تُحاكم إليه تلك الدّعوات المختلفة، وقد اعتُمد في هذه الدّراسة على الاستقراء والتّحليل لأقوال الأئمّة وتصرّفاتهم، فخلُص البحث إلى أنّ أهمّ مقاصد علم أصول الفقه العنايةُ بالدّليل وحسن استعماله، وذلك ببيان المنهج الأقوم لاستنباط الأحكام الشّرعيّة، وبناء منهج التّفكير العلميّ السّليم، ممّا يُبعد العبد عن اتّباع الهوى، وهذا ما يقضي على النّزاع والفوضى، وبذلك يمكن التّمييز بين التّجديد المحمود، والتّجديد المذموم، إذ يستهدف الأوّل إبعاد الدّخيل، وتنقية العلم من كلّ ما يعيق تحقيق مقاصده، بينما يؤدّي الثّاني إلى هدم العلم، لكونه يضادّ تلك المقاصد.
The principles of jurisprudence, as a science, grew up and became mature in a purely islamic environment; and over time, Mishandling this science has been noticed, a thing that necessitated calls for its renewal especially in our era. This thesis aims to reveal the objectives of this science so as to be a criterion or a standard by which these calls are judged. This study relied on the induction and analysis of imams' sayings and actions. The research came to a conclusion that the most important objectives of the principles of jurisprudence are paying attention to the evidence and its proper use, by showing the most appropriate approach to derive legal rulings and building a sound scientific thinking approach; this keeps the human being far from following their desires and eliminates conflicts and chaos(anarchy); thus it is possible to distinguish between praiseworthy renewal and blameworthy renewal as the former aims to remove or banish the intruder and purify science of everything that prevents the achievement of its objectives; while the second leads to the destruction of science since it contradicts those objectives.
Keywords: مقاصد، أصول الفقه، التّجديد الأصولي.; objectives; principles of jurisprudence; renewal.